FORENSIC DOCUMENT EXAMINATION IN ECONOMIC CRIME INVESTIGATIONS - Artem Kovalenko; Mykola Zhdan; Oleksandr Shapovalov (Baltic Journal of Economic Studies)
Despite the extensive digital transformation of the economy, physical documents (typically on a tangible medium such as paper or polymer) remain a significant component of document flows in economic sphere. Accordingly, these documents inevitably play a role in economic crimes, serving as objects or instruments of offenses, carrying traces of criminal activity, or representing unlawful proceeds obtained from such crimes. In economic investigations, such documents constitute valuable evidence that requires thorough examination using specific procedural and forensic tools. Thus, the purpose of the article is to identify and present the means of forensic document examination in economic crime investigations. The study employs a combination of general and specialized scientific methods. Using the formal-legal approach the authors clarify the procedural status of physical documents as evidence under the current Ukrainian criminal procedure legislation. The authors employ a formal-logical approach to differentiate preliminary, expert, and judicial examinations of documents. Through the modeling, hypothetical scenarios of the activities of authorized persons involved in document examination during economic investigations were constructed. The results of the study show that in criminal proceedings, documents are considered written (documentary) evidence when their content is of importance to the case, and physical evidence when their external characteristics – such as material, production method, security features, signs of forgery, damage, etc. – possess evidentiary value. The authors identify typical documents to examine in economic crime investigations, including corporate founding and administrative documents, accounting and tax records, banking documents, securities, correspondence, identity documents, audit findings, and inspection reports, among others. During pre-trial investigation, a preliminary examination of such documents is conducted through visual perception (reading, observing) as part of a formal inspection procedure. The study also examines the possibilities of involving specialists (forensic scientists, economists, computer scientists) and the use of specialized technical tools during the inspection of documents in economic investigations. It is established that an in-depth expert examination of documents is carried out by referring them for forensic expertise. Technical document examination and handwriting expertise help determine a document’s authenticity and authorship; forensic economic expertise clarifies the content of financial transactions recorded in the documents; forensic commodity expertise is used to determine the value of securities.